The Public Perception of Traffic Jam in Kuala Lumpur Malaysia - Hasmita, Lia; Radzuan, Nur Afinie Binti (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this study was to analyze and describe the public perception of traffic jam in Kuala Lumpur, Malaysia, and analyze the factors that caused traffic jam in Kuala Lumpur, Malaysia. This research is a qualitative descriptive study. Data collection techniques use observation, interviews and documentation as data collection instruments. Furthermore, the data will be analyzed using qualitative descriptive analysis. The type of data used is primary data. Primary data in the form of observations, interviews and documentation. The results of this study revealed 1) public perception of traffic jam in Kuala Lumpur, Malaysia, the condition of traffic jam in Kuala Lumpur Malaysia is still quite severe, especially during rush hours, among others, in the morning when people leave for work, go to school and others etc., during the day during lunchtime, and in the afternoon when people will return home. Jam also occurs around tourist attractions in Kuala Lumpur, Malaysia. 2) Factors causing traffic jam in Kuala Lumpur, Malaysia, caused by the increasing ownership of private vehicles, the low price of cars, public vehicles do not have their own lines. And the community is still reluctant to use public transportation.